Two Indias: The structure of primary health care markets in rural Indian villages with implications for policy. (May 2022) - Das, Jishnu; Daniels, Benjamin; Ashok, Monisha; Shim, Eun-Young; Muralidharan, Karthik
Abstract: We visited 1519 villages across 19 Indian states in 2009 to (a) count all health care providers and (b) elicit their quality as measured through tests of medical knowledge. We document three main findings. First, 75% of villages have at least one health care provider and 64% of care is sought in villages with 3 or more providers. Most providers are in the private sector (86%) and, within the private sector, the majority are 'informal providers' without any formal medical training. Our estimates suggest that such informal providers account for 68% of the total provider population in rural India. Second, there is considerable variation in quality across states and formal qualifications are a poor predictor of quality. For instance, the medical knowledge of informal providers in Tamil Nadu and Karnataka is higher than that of fully trained doctors in Bihar and Uttar Pradesh. Surprisingly, the share of informal providers does not decline with socioeconomic status. Instead, their quality, along with the quality of doctors in the private and public sector, increases sharply. Third, India is divided into two nations not just by quality of health care providers, but also by costs: Better performing states provide higher quality at lower per-visit costs, suggesting that they are on a different production possibility frontier. These patterns are consistent with significant variation across states in the availability and quality of medical education. Our results highlight the complex structure of health care markets, the large share of private informal providers, and the substantial variation in the quality and cost of care across and within markets in rural India. Measuring and accounting for this complexity is essential for health care policy in India. Highlights: In 2010, the average Indian village had 3.2 primary healthcare providers. Of these, 86% were in the private sector and 68% had no formal medical training. In richer states, the share of informal providers did not decrease—quality improved. In high-performing states, quality was higher and per-patient costs were lower. The density and variation of health market cost and quality has policy implications.